CUSTOMER LOYALITY ANALYSIS AND BUSINESS PROCESS IMPROVEMENT USING RETURN ON QUALITY METHOD IN INSURANCE COMPANY - Moses L. Singgih (Jurnal Teknobisnis, 2012)
The competition in the insurance business today occurs as a result of technological advances, deregulation and the changing needs of the market. Thus the future business environment will be very competitive to acquire market share. The company management needs to be critical for factors such as retention, is a parameter to determine the level of satisfaction and a high level of loyalty to a product / service. Therefore, based on the theory, the researchers want to know the level of satisfaction and loyalty of these insurance companies. Return on Quality method has been applied to measure retention rate resulting from quality improvement programs, market share and loyalty. The proposed improvements program are include making the database of agents field agents coaching and competent recruitment agents. As a ROQ calculation result, showed that the program was feasible, yet it was not sensitive to interest rates.